PERENCANAAN DAN PENATAAN RUANG PARKIR UNIVERSITAS TRIBHUWANA TUNGGADEWI MALANG - Rifky Aldila Primasworo Rifky Aldila Primasworo; Andy Kristafi Arifianto Andy Kristafi Arifianto; Karolina Nay Karolina Nay (Universitas Islam Balitar Blitar, 2021)
Tribhuwana Tunggadewi University Malang is one of the private universities in Malang which has a growing number of students which continues to increase every year which has an impact on the availability of parking spaces on campus. The problem that occurs is that the increasing number of vehicle users has an impact on the increase in the need for parking available on campus In existing conditions, it is not enough to accommodate the number of vehicles, especially on certain lecture days and when there are campus activities that invite many vehicles to enter, such as during graduation events or other activities. The characteristic analysis of car parking is that 919,505 m² can produce 38 SRP, while for a motorcycle parking area which has an area of 834.65 m² it can produce 401 SRP. The number of parking space requirement for both four-wheeled and two-wheeled vehicles in the next 10 years has increased every year with the results of the analysis of the number of students are 15.4597 people in 2030 from 8744 people in 2020 so that the need for vehicle parking spaces in the next 10 years will reach 65 SRP with A capacity of 39 SRP is available for cars and 723 SRP with a current parking capacity of 405 SRP for two-wheeled vehicles.